2005
DOI: 10.1196/annals.1333.090
|View full text |Cite
|
Sign up to set email alerts
|

High‐Dose Thiamine Therapy Counters Dyslipidemia and Advanced Glycation of Plasma Protein in Streptozotocin‐Induced Diabetic Rats

Abstract: The streptozotocin-induced (STZ) diabetic rat experimental model of diabetes on insulin maintenance therapy exhibits dyslipidemia, mild thiamine deficiency, and increased plasma protein advanced glycation end products (AGEs). The reversal of thiamine deficiency by high-dose thiamine and S-benzoylthiamine monophosphate (benfotiamine) prevented the development of incipient nephropathy. Recently, we reported that high-dose thiamine (but not benfotiamine) countered diabetic dyslipidemia. To understand further the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 25 publications
4
32
1
1
Order By: Relevance
“…A study by Beisswenger et al (23), conducted in people with diabetes, showed that hyperglycemia rapidly induces in vivo synthesis of dicarbonyls, which are highly reactive AGE precursors such as MG and 3-deoxyglucosone. Benfotiamine decreased dicarbonyls formation in animal models (41). In our study, the postprandial circulating MG levels increased maximally at 4 h, an effect prevented by benfotiamine.…”
Section: Correlationsmentioning
confidence: 51%
“…A study by Beisswenger et al (23), conducted in people with diabetes, showed that hyperglycemia rapidly induces in vivo synthesis of dicarbonyls, which are highly reactive AGE precursors such as MG and 3-deoxyglucosone. Benfotiamine decreased dicarbonyls formation in animal models (41). In our study, the postprandial circulating MG levels increased maximally at 4 h, an effect prevented by benfotiamine.…”
Section: Correlationsmentioning
confidence: 51%
“…CML residue concentrations in plasma protein and haemoglobin were also linked to 3DG-H residue concentrations and to pentosidine residue concentration in haemoglobin. CML and CEL residues in plasma protein may be formed from lipid-derived precursors without apparent mediation by glyoxal and methylglyoxal [36].…”
Section: Discussionmentioning
confidence: 99%
“…Thiamine and a benfotiamine supplement prevented tissue accumulation and increased the urinary excretion of protein glycation, oxidation and nitration adducts associated with experimental diabetes [175]. Karachalias et al [176] reported that the hydroimidazolone of AGE residues derived from glyoxal and methylglyoxal (G-H1 and MG-H1, respectively) increased by 115% and 68%, respectively, in streptozotocin-induced diabetic rats, and thiamine and benfotiamine normalized these residues. However, Ncarboxymethyl-lysine (CML) and N-carboxyethyl-lysine (CEL) residues increased by 74% and 118%, respectively, in diabetic-induced rats, and only thiamine normalized these residues.…”
Section: Other Rolementioning
confidence: 99%